An Analysis of Amenity Standards Compliance in Meat Tourism Village Based on Regulation No. 3/2022 - Pardede, Ester Elisabeth; Ita Bina Anakampun, Ahmad Sapreza, Sabrina Pinem, Vinsessius Tryan Amsit Hulu, (Program Pascasarjana STIE Amkop Makassar, 2026)
This study analyzes the compliance of tourism amenity development in Meat Tourism Village with the standards stipulated in Regulation Number 3 of 2022. Adopting a qualitative evaluative approach, data were collected through field observations, semi-structured interviews, and document analysis. A compliance matrix was developed to compare regulatory requirements with actual field conditions. The results indicate a moderate level of compliance, with 55% of assessed indicators categorized as compliant, 33% partially compliant, and 12% non-compliant. While core physical infrastructure such as parking areas, gazebos, public spaces, and pedestrian pathways has been established, gaps remain in maintenance systems, waste management, and informational support. These findings suggest that physical development alone does not ensure sustained regulatory adherence; effective governance, routine maintenance, and continuous monitoring are essential. This study contributes to tourism infrastructure governance evaluation by integrating regulatory compliance assessment with policy implementation perspectives, providing practical insights for improving amenity management in tourism villages. Keywords : Amenity Standards; Governance, Regulatory; Compliance; Sustainable Tourism; Tourism Village